Building Skills to be Consistent in Students' Digital Information by Utilizing The Wikipedia Online Encyclopedia (EOW) on The Material of The Sensory System - Geolita, Pimpi; Hizqiyah, IYN; Toharudin, U (Jurnal Report of Biological Education, 2024)
Background: This research is motivated by the lack of students being consistent in seeking digital information during learning, especially in terms of solving problems and understanding the issues of the problems given. The purpose of the study was to measure the skills of being consistent in searching for digital information and the achievement of students' learning outcomes in solving a problem. Method: The method used is quantitative experiment in the form of Pre-Experiment Design. This study involved 28 students of XI MIPA 3 SMAN 1 Katapang. The review of the sub-indicators of being consistent in finding digital information was carried out with a One Shot Study of observation and scoring on the observation sheet instrument, while the method used to examine students' mastery of concepts was the One Group Pretest-Posttest design, using instruments in the form of multiple choice questions. Results: The results of this study show that the average value of consistent skills in finding digital information of students is 76, pretest 39.61, posttest 81.18, and the knowledge improvement index (N-gain) was dominated by medium (0.60). Students' positive response to learning received an overall average score of 80.4. Conclusion:  Thus, learning with the use of Encyclopedias Online Wikipedia (EOW) is effective for improving student learning outcomes on the material of the Sensory System. Keywords : Consistent attitude skills; Encyclopedias Online Wikipedia (EOW); Material of the Sensory System